Experimental investigation of microbubble generation in the venturi nozzle. (June 2019) - Lee, Chang Hun; Choi, Hong; Jerng, Dong-Wook; Kim, Dong Eok; Wongwises, Somchai; Ahn, Ho Seon
Highlights: The Venturi nozzle design with entry and exit angles, which leads the self-sucked air flow. Microbubbles generation regarding to entry and exit angles. High speed visualization study to track the self-sucked air flow stream broken into microbubbles. Abstract: We studied the effect of varying the entry and exit angles of Venturi nozzles on the formation of microbubbles in Venturi nozzle-type microbubble generators. We 3D-printed nozzles with five entry angles (15, 22, 30, 38 and 45°) and five exit angles (15, 22, 30, 38 and 45°). For the visualization experiment, we inserted the nozzles into a cover case made of aluminum and transparent acrylic. We measured the pressure drop and the air flow rate with respect to the entry and exit angles, determined the diameters of the bubbles using a digital camera, and analyzed bubble breakage by observing the behavior of the bubbles using a high-speed camera. We confirmed that the exit angle (not the entry angle) is dependent on the pressure drop and found that the air flow rate did not vary linearly with the fluid flow rate, as expected according to Bernoulli's theorem. Instead, it tended to remain constant or decrease as the fluid flow rate increased due to the abnormal flow. The sizes of the bubbles decreased as the exit angle increased, except in cases where the outlet angle was greater than 30° at high flow rates (260–300 LPM). We observed a change in bubble size with respect to exit angle. According to our visualization, the bubbles were broken by the flow separation at the beginning of the divergence at the exit.